Community Policing and Internal Security in Delta and Edo States of Nigeria - Goodluck Irorohwo Oyibokure; Onofere Princewill Okereka; Akpomuvire Mukoro (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2023)
This study investigated the effect of community policing as supportive strategy in combating security challenges in Delta and Edo States of Nigeria. A cross-sectional research design and the probability sampling technique were adopted. A questionnaire was employed as the research instrument for this study with 317 respondents deemed usable. Data collected were analyzed using simple regression analysis with the aid of Statistical Package for Social Sciences (SPSS) software version 23.0. The results of the study revealed that police inefficiency positively and significantly influences human insecurity in the country; the structure of the Nigeria police positively and significantly impacts the ineffective police security service delivery in the country, The present security challenges in the country positively and significantly influences the clamour for community policing in the country and the community policing positively and significantly influences improve internal security in the country. The study concludes that keeping peace and maintaining safety of citizens and property cannot be over emphasized for the progress and survival of any sovereign nation. It can be viewed as a precondition for good governance leading to socio-economic growth, political advancement, national peace building, human capital development, human freedom and proper functioning of things in a country. There will be no doubt therefore, that absence of internal security breeds disorder, increase insecurity, distorts freedom, reduce human value, and impoverish the citizens. Thus, the study recommends among others that the implementation of community policing programme should be beyond mere rhetoric. Therefore, the government should allocate more funds and resources to support the operations of community poling. Moreover, more motor vehicles and other security gadgets should be procured to enhance police patrol.